Efficacy of Ketogenic Diet for Infantile Spasms in Chinese Patients With or Without Monogenic Etiology - Wang, Jun; Zhang, Jie; Yang, Ying; Gao, Kai; Wu, Ye; Zhang, Yuehua; Jiang, Yuwu (Frontiers in Pediatrics, 2022)
Objective: This study aimed to assess the efficacy of ketogenic diet (KD) for infantile spasms (IS) infants with and without different pathogenic gene mutations. Methods: We retrospectively evaluated the data of 119 infants with IS who underwent whole-exome sequencing (WES) after 16-week KD treatment, including the genotype and phenotype information. Results: The responder rate to KD in 119 patients was 47.90%. The responder rate in female patients (60.47%) was significantly higher than that in male (p = 0.04). There were no significant differences (46.88% vs. 48.28%) between responder rates in patients with (n=32, 26.89%) and without identified genetic mutation (n=87, 73.11%), but there were significant differences in responder rates to KD for different sexes (p = 0.01) and age of seizures (p = 0.01). Patients with CDKL5 mutations showed a significantly better response to KD (87.50%) than patients without CDKL5 mutations (p=0.03). Responder rates to KD with ALG13 mutations were higher than those without the same gene mutations, while the scenario was reversed in cases with mutations in KCNT1, SLC35A2, PCDH19, and STXBP1. Seven of 8 patients with CDKL5 mutations were responders, including 5 mutations located in functional motifs, and 2 mutations in the catalytic domain. Conclusion: KD therapy was effective in infants with IS. Female patients tended to response better to KD. WES yielded a higher diagnostic rate among younger and female IS patients. Patients with CDKL5 and ALG13 mutations had the highest responder rates to KD, whereas patients with STXBP1 mutations had the lowest rate. Patients with CDKL5 mutations presumably influencing the functional motifs were more likely to be the responders to KD.